Research Advances and Perspectives on Terahertz Detection based on 2D Materials - Zhuoxuan Chen; Zelong Li; Muhammad Ahsan Iqbal; Nayab Arif; Chenyang Xing; Lu Qi; Yu‐Jia Zeng (Advanced Physics Research)
Abstract Terahertz (THz) detection offers unique advantages in penetrating materials opaque to visible light and infrared radiation, which is crucial for applications in security, medical imaging, and material analysis. Despite challenges posed by a lack of suitable optical materials, recent strides in 2D materials, such as graphene, transition metal dichalcogenides (TMDCs), and topological materials, show promise in overcoming these limitations. This review critically examines the exceptional optical and electrical properties of 2D materials, and surveys recent advancements in 2D THz optoelectronics. Finally, the key challenges and prospects in this burgeoning field of research are discussed.